Effects of Different Pelleted Diets and Pellet Size on Bird Performance - Sundu, B; Kumar, A; Dingle, J (ANIMAL PRODUCTION, 2009)
An experiment investigated performance of birds fed the pelleted corn-soy diet versus the pelleted 30% copra meal based diet with different pellet sizes. This study was conducted for six weeks. A total of 144 male day old chicks were used in this trial. One day old birds were randomly allocated to four treatment diets with six replications. The starter and grower pelleted diets were with or without 30% copra meal and in two forms, either fine or mixed sized particles. The experimental design was a two way factorial with two basal diets, two particle sizes and six replicate cages of six birds per treatment. The inclusion of 30% copra meal in the pelleted diet decreased body weight and feed intake, but improved feed eficiency. Grinding the diet to a fine pellet size impaired the body weight and feed intake. The effect of pellet size became more evident when the birds grew older. Birds fed the pelleted form of copra meal accelerated their growth rate so that they were not significantly different from the weight of birds fed the pelleted form of the corn-soy diet. However the feed intake of birds fed the pelleted copra meal diet was lower than the feed intake of those fed the pelleted corn soy diets. It was concluded that inclusion of copra meal in the diet impaired growth of birds, particularly in the starter phase. Pelleting and crumbling copra meal diet could increase the bird performance to the same level of the performance of birds fed the pelleted corn-soy control diet while fine grinding the pelleted diet reversed this trend. (Animal Production 11(3): 165-169 (2009)Â Key Words: broilers, pellet diet, pellet size, copra meal